Facing the 60th Lithuanian Mathematical Society (LMD) conference: a glance at the past - Banionis, Juozas (Lietuvos matematikos rinkinys, 2018)
In this article, based on the sources stored at the funds of Lithuanian mathematical museums (with Henrikas Jasiūnas’s name) based in Vilnius University, reveals the genesis of the Lithuanian Mathematical Society, its origins are the manifestations of the unification of previous mathematicians of the previous year.